AJCO : Association des jeunes chirurgiens oncologues - Thomas Sorin; Olivier Camuzard; Adnan El-Bakri; Thomas Sagardoy; Antoine Legras (Bulletin du Cancer, 2015)
Cabozantinib is a multikinase inhibitor with high efficacy in patients with metastatic renal cell carcinoma. We present the case of a 53-year-old patient undergoing second-line treatment for metastatic renal cell carcinoma who presented with extensive skin lesions consistent with Stevens-Johnson syndrome, confirmed by biopsy. He presented a torpid course, progressing to toxic epidermal necrolysis and subsequent death despite supportive measures and immunoglobulin treatment. Although cabozantinib can cause skin reactions, such torpid and aggressive reactions as those observed in this clinical case have not been reported.